2014
DOI: 10.1039/c3ob42416b
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine antibiotic inspired discovery of potent bromophenazine antibacterial agents against Staphylococcus aureus and Staphylococcus epidermidis

Abstract: Nearly all clinically used antibiotics have been (1) discovered from microorganisms (2) using phenotype screens to identify inhibitors of bacterial growth. The effectiveness of these antibiotics is attributed to their endogenous roles as bacterial warfare agents against competing microorganisms. Unfortunately, every class of clinically used antibiotic has been met with drug resistant bacteria. In fact, the emergence of resistant bacterial infections coupled to the dismal pipeline of new antibacterial agents ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 15 publications
(22 reference statements)
1
95
0
Order By: Relevance
“…In previous studies, we found that some ester groups are well-tolerated while ether- or amine-group substitution of the phenolic hydroxyl group leads to a complete loss of antibacterial activities 22 . The structural requirement for a 1-hydroxyl group (or masked ester/carbonate) on the HP scaffold, coupled with the results from UV-Vis experiments and metal(II) co-treatment MIC profiles, leads us to conclude that non-metal(II) binding carbonates 24 and 25 are prodrugs that release metal(II)-chelators HP 1 and 17 , which bind metal(II)-cations and eradicate planktonic and biofilm cells against susceptible, Gram-positive human pathogens.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In previous studies, we found that some ester groups are well-tolerated while ether- or amine-group substitution of the phenolic hydroxyl group leads to a complete loss of antibacterial activities 22 . The structural requirement for a 1-hydroxyl group (or masked ester/carbonate) on the HP scaffold, coupled with the results from UV-Vis experiments and metal(II) co-treatment MIC profiles, leads us to conclude that non-metal(II) binding carbonates 24 and 25 are prodrugs that release metal(II)-chelators HP 1 and 17 , which bind metal(II)-cations and eradicate planktonic and biofilm cells against susceptible, Gram-positive human pathogens.…”
Section: Resultsmentioning
confidence: 95%
“…Based on our previous studies, we have found that the HP scaffold 1 requires the 1-hydroxyl group and 2-bromine atom to demonstrate antibacterial activities 22, 25 . In addition, the 4-position is highly active when containing a bromine atom (i.e., HP 1 ), but can also tolerate a butyl group (i.e., HP 2 ) 25 which motivated these investigations as Wohl-Aue reactions could provide synthetic avenues to both 4-brominated and 4-methylated HPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…244 This lead inspired further DTS work resulting in a variety of halogenated phenazine analogs (Figure 32), many of which exhibited low micromolar activities against various resistant Gram-positive bacteria. 245 …”
Section: Targeting Quorum Sensing and Bacterial Signalingmentioning
confidence: 99%
“…3,4 The ability of such small molecules to keep competitors in check through the generation of reactive oxygen species (ROS) has attracted attention for new drug development. 3,5 ROS including superoxide radical O 2 −• , hydrogen peroxide H 2 O 2 , and hydroxyl radical • OH are generated as a natural consequence of respiration but can cause cellular damage at elevated levels (Scheme 1). 6 Potentiating these ROS in cancers using small molecules has been considered as a possible drug design strategy.…”
mentioning
confidence: 99%